Analisis Kadar Fenolik Total dari Ekstrak Etanol dan Ekstrak Terpurifikasi Daun Oyong (Luffa acutangula (Linn.) Roxb.) - Ridha Istiqomah; Novena Lindawati; Nastiti Utami (Indonesian Journal on Medical Science, 2023)
Secondary metabolites found in oyong leaves (Luffa acutangula (Linn.) Roxb.) include  phenolics, flavonoids, saponins, terpenes and tannins. Phenolic compounds have an important role as antioxidants. Antioxidant be able to protect the body from degenerative diseases caused by cell damage due to free radicals. Extract that undergo a purification process will give the different levels of total phenolic to the crude extract. In this research, the total phenolic content of ethanol extract and purified extract of oyong leaves will be determined. Maceration with 96% ethanol was used as an extraction technique. The liquid extraction technique was employed for extract purification, with warm water, n-hexane and ethyl acetate serving the solvent. The phenolic content was detected by Thin Layer Chromatography (TLC), the stationary phase of silica gel , the geraneous phase of n-hexane : ethyl acetate : methanol (2:7:2). Phenolic content was measured using UV-Vis Spectrophotometry, Folin-Ciocalteau reagent and standard gallic acid. The total phenolic levels obtained in the ethanol extract and purified extract of oyong leaves were (34,000 ± 0,350) mg GAE/gram extract and (40,117 ± 0,195) mg GAE/gram extract. Purified extract have higher levels because pass through a purification stage which produce pure extract with higher compound content.